Norm focusing and losses—Evidence of ultimatum game experiments - Kierspel, Sabrina; Neumann, Thomas; Windrich, Ivo; Berger, Roger; Vogt, Bodo (Frontiers in Behavioral Economics, 2024)
Human decision-making pertaining to gains compared to those pertaining losses is shown to be quite different. However, mixed evidence is provided regarding the effect on the decision-makers’ prosocial behaviors; that is, losses are shown to either increase or decrease prosocial behaviors. In this context, the effect of social norms on observed behavior can play a crucial role. To examine this aspect in more detail, we conducted incentivized ultimatum game experiments and analyzed data from three treatments, the control treatments (without specific norm focus), and two different norm-focus treatments (“Average behavior” treatment and “Self-interested behavior” treatment). In total, 550 participants took part in our experiment. Basically, we found no significant difference between the division of gains and losses in the “Control” and “Self-interested behavior” treatments. However, we found such a difference in the “Average behavior” treatment. In addition, we found that inducing a norm focus leads to less variance in proposers’ behavior and a greater concentration of their demands around the induced norm in the “Average behavior” treatment. In contrast, we found a higher variance in proposers’ behavior in the “Self-interested behavior” treatment. In terms of responders’ behaviors, we observed a tendency toward a higher frequency of responders’ rejections in the loss domain compared to the gains domain.